Online Learning Stress and Student Performance: The Moderating Role of Emotional Intelligence - Nasir, Palwasha; Khan, Muhammad Usman; Siddique, Ayesha (Journal of Global Social Transformation, 2026)
This take a look at turned into a quantitative examine that checked out the correlation among the pressure associated with on-line studying and the instructional overall performance of the scholars with emotional intelligence (EI) performing as a mediating variable among the college college students of Islamabad in Pakistan. With stratified random sampling, three hundred college students have been received in six universities, 3 of that are public and 3 are private. The respondents took five-factor Likert-scale proven measures of on line gaining knowledge of pressure, emotional intelligence, and educational overall performance. The records evaluation become performed via way of means of the usage of IBM SPSS and structural equation modeling (SEM) with the descriptive, Cronbach alpha reliability evaluation facts, Pearson correlation, and moderated regression evaluation with bootstrapped self assurance intervals. Findings indicated that pressure on on line mastering become a prime and bad indicator of instructional overall performance. This courting become tremendously moderated via way of means of emotional intelligence, wherein an expanded degree of EI buffered college students towards the bad consequences of on line studying on their overall performance. Interaction of pressure and EI became enormous and bootstrapped self assurance c program languageperiod supported the electricity of the moderation effect. These effects have enormous implications at the coverage of virtual education, scholar health offerings and the layout of emotional touchy on-line getting to know in Pakistani tertiary education.